Condensation with two constraints and disorder. (17th April 2018) - Barré, J; Mangeolle, L
Abstract: We consider a set of positive random variables obeying two additive constraints, a linear and a quadratic one; these constraints mimic the conservation laws of a dynamical system. In the simplest setting, without disorder, it is known that such a system may undergo a 'condensation' transition, whereby one random variable becomes much larger than the others; this transition has been related to the spontaneous appearance of non linear localized excitations in certain nonlinear chains, called breathers. Motivated by the study of breathers in a disordered discrete nonlinear Schrödinger equation, we study different instances of this problem in presence of a quenched disorder. Unless the disorder is too strong, the phase diagram looks like the one without disorder, with a transition separating a fluid phase, where all variables have the same order of magnitude, and a condensed phase, where one variable is much larger than the others. We then show that the condensed phase exhibits various degrees of 'intermediate symmetry breaking': the site hosting the condensate is chosen neither uniformly at random, nor is it fixed by the disorder realization. Throughout the article, our heuristic arguments are complemented with direct Monte Carlo simulations.